2006
DOI: 10.1182/blood-2006-03-011437
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressant drug FTY720 inhibits cytosolic phospholipase A2 independently of sphingosine-1-phosphate receptors

Abstract: FTY720 is a potent immunomodulator drug that inhibits the egress of lymphocytes from secondary lymphoid tissues and thymus. FTY720 is phosphorylated in vivo by sphingosine kinase 2 to FTY720-phosphate, which acts as a potent sphingosine-1-phosphate (S1P) receptor agonist. However, in contrast to S1P, FTY720 has no effect on mast-cell degranulation, yet significantly reduces antigen-induced secretion of PGD 2 and cysteinyl-leukotriene. Unexpectedly, this effect of FTY720 was independent of its phosphorylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
101
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 69 publications
4
101
0
1
Order By: Relevance
“…It is however very possible that the significant intracellular accumulation of this substance described by our data, may explain part of the surprising therapeutic efficacy of even low dosage levels in MS as compared to its formerly applied dosage in transplantation (Kappos et al, 2010). Therefore, by interpreting our findings in a positive direction, Fingolimod may affect immune cell-relevant intracellular targets, such as phospholipase A2 (PLA2) and protein phosphatase 2A (PP2A) (Payne et al, 2007;Saddoughi et al, 2013;Arlt et al, 2014). These results have to be further confirmed by an in vivo model, e.g.…”
Section: Discussionmentioning
confidence: 80%
“…It is however very possible that the significant intracellular accumulation of this substance described by our data, may explain part of the surprising therapeutic efficacy of even low dosage levels in MS as compared to its formerly applied dosage in transplantation (Kappos et al, 2010). Therefore, by interpreting our findings in a positive direction, Fingolimod may affect immune cell-relevant intracellular targets, such as phospholipase A2 (PLA2) and protein phosphatase 2A (PP2A) (Payne et al, 2007;Saddoughi et al, 2013;Arlt et al, 2014). These results have to be further confirmed by an in vivo model, e.g.…”
Section: Discussionmentioning
confidence: 80%
“…Whereas several studies support its effects on lymphocyte trafficking, more recent investigations indicate that the FTY720 action distinct from S1P might not only be due to its interaction with other S1PR subtypes but may be based on direct intracellular effects on e.g., the S1P lyase or the cytosolic PlA 2 (33,43). For S1P it has recently been documented that the S1P-S1P 1 axis mediates many of the T cell-associated activities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the definition of T lymphocytes as the prime and major target of FTY720/S1P has been challenged by several publications showing significant effects on other immune competent cells comprising monocytes and dendritic cells (DC) (26 -28, 31-33). These investigations raise the possibility that not only migratory but rather differentiating effects are involved early during an immune response, which include e.g., a direct intracellular blockade of cPLA2 that is independent of FTY720 phosphorylation and significantly contributes to its therapeutic activity in experimental autoimmune encephalomyelitis (33).…”
mentioning
confidence: 99%
“…4 In agreement, FTY720-phosphate, an agonist of all S1P receptors except S1P 2 , did not induce degranulation. 19 Moreover, quantitative real-time PCR (QPCR) revealed that like rodent MCs, LAD2 cells as well as cord blood-derived human MCs and human skin MCs express similar levels of S1P 1 and S1P 2 , but do not express S1P 3-5 receptors (data not shown). S1P at 1 M was nearly as effective as Ag or ionomycin at stimulating secretion of TNF-␣ and IL-6 ( Figure 1B,C For personal use only.…”
mentioning
confidence: 99%